Diagnóstico dos aspectos cognitivos afetivos e sociais que impulsionam a aprendizagem em processos de educação em Ensino de Ciências na Amazônia - Tavares, Maria Trindade dos Santos (2011)
This research was made at an elementary school from the city of Manaus state schools system and its purpose was constructing a diagnosis of the cognitive, affective and social aspects which propel the learning in the First Years of the Elementary School, evidencing elements that may be helpful to the learning process in the Teaching of Sciences. In order to do so, a qualitative research approach was adopted, since it is perceived as a process of analyzing and reflecting over reality. Interviews and questionnaires, applied to teachers of the first years of the Elementary School Teaching in the school environment itself, were the instruments used to collect data for the research. The findings after the analysis led to conclusion that the cognitive, affective and social aspects, characteristic of the pedagogical practices in the school routine, propel the learning process, contributing to make the teachers reflect about their own practice and school context.